STRIVING FOR EQUILIBRIUM: THE LEADERSHIP TRANSITION FROM JOKOWI TO ANIES AND THE DYNAMIC INTERPLAY OF DEMOCRACY AND LEGAL JUSTICE - Abdul Manap; Nahot Tua Parlindungan Sihaloho; Muhammad Syafri; Adie Nurjana Resma; Trusti Dhiani Henartiwi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study meticulously examines the intricate interplay between democracy and legal justice during the leadership transition from Jokowi to Anies in Country X, aiming to achieve governance equilibrium. The investigation encompasses a rich historical context, delving into the factors that have shaped the political landscape leading to this pivotal moment. Leveraging insights from a comprehensive public sentiment survey, the research captures the pulse of the population, discerning their expectations and concerns. The unprecedented approval ratings enjoyed by Jokowi became a focal point, not merely as a measure of personal popularity but as a broader endorsement of democratic processes. As Anies assumes leadership, the study aims to evaluate the continuity or evolution of democratic principles, offering insights into the democratic legacy established by Jokowi. The intrinsic link between democracy and legal justice forms a central theme, exploring how these elements converge or diverge during the transition. Comparative analyses with international cases enrich the study by providing global perspectives on governance dynamics. Critical evaluations of existing research identify gaps, paving the way for future scholarly inquiries. This research seeks to contribute a nuanced understanding of the dynamic relationship between democracy and legal justice, offering valuable insights into political science, governance studies, and leadership dynamics globally.